Status dystonicus due to missense variant in ARX: Diagnosis and management. (September 2018) - Gorman, Kathleen M.; Cary, Heather; Gaffney, Laura; Forman, Eva; Waldron, Dympna; Al-Delami, Fowzy; Lynch, Bryan J.; King, Mary D.; Allen, Nicholas M.
Abstract: Movement disorders are increasingly identified in infantile encephalopathies due to single gene disorders (e.g. SCN2A, CDKL5, ARX ). The associated movement disorder can be challenging to recognise and treat. We report a 2 year-old boy with a background history of Ohtahara syndrome due to a missense variant in ARX (the aristaless-related homeobox gene) who subsequently developed status dystonicus. ARX is a transcription factor that plays a critical role in cortical neuronal development and is associated with a range of important neurodevelopmental disorders depending on the site of the pathogenic variant. Cases of status dystonicus are described with variants affecting the polyalanine expansion region of ARX but have not been reported previously with variants affecting the aristaless domain of ARX as in this case. Dystonic episodes posed a challenge in recognition and treatment, including confusion with status epilepticus. We discuss the difficulties in diagnosis and management of status dystonicus, an underreported life-threatening emergency in children. Highlights: Variants in ARX are an important cause of severe early-onset epilepsy, developmental delay and dystonia. We report status dystonicus in male with Ohtahara syndrome due to a missense variant in ARX, expanding the genotype-phenotype. Status dytonicus is a " medical emergency", requiring early recognition, supportive and dystonia-specific treatments.